Legal Sanction Application against Perpetrators of Verbal Sexual Harassment (Catcalling) in Indonesia - Mohammad Ridhoni Djafar; Fenty U Puluhulawa; Zamroni Abdussamad (International Journal of Law, Crime and Justice, 2025)
Catcalling or verbal sexual harassment is a social phenomenon that is rampant in Indonesia. It involves unwanted sexualized remarks that dehumanize the victim and can have a psychological impact. Although Law Number 12 of 2022 on Criminal Acts of Sexual Violence (UU TPKS) has regulated non-physical sexual harassment in Article 5, its application in the field still faces various obstacles. This study aims to determine the legal formulation of the application of sanctions against perpetrators of verbal sexual harassment (catcalling). This research uses an empirical normative approach. The results show that the legal formulation of the application of sanctions against perpetrators of verbal sexual harassment has progressed with explicit regulation in Article 5 of Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (TPKS Law). To realize substantive and effective justice, it is necessary to improve the formulation of sanctions, integrate non-criminal sanctions, increase the capacity of law enforcers, and strengthen public education.